Optimalisasi Literasi dan Numerasi melalui Penerapan Inquiry-Based Learning pada Jenjang Sekolah Dasar - AYU HARTINI (Bahasa Indonesia, 2026)
ABSTRACT: Inquiry-Based Learning (IBL) is a student-centered instructional approach that encourages learners to actively engage in questioning, investigating, exploring, and constructing knowledge through problem-solving activities. This study aims to examine the effectiveness of the Inquiry-Based Learning model in enhancing literacy and numeracy competencies among elementary school students. Literacy is understood as the ability to access, interpret, evaluate, and communicate information critically, while numeracy refers to the capacity to apply mathematical concepts and reasoning in various contexts. The research employs a qualitative literature review method by analyzing relevant scholarly articles, books, and research reports related to Inquiry-Based Learning, literacy, and numeracy development. The findings indicate that the implementation of IBL contributes positively to the improvement of students’ critical thinking, analytical abilities, problem-solving skills, and conceptual understanding in both literacy and numeracy domains. Compared to conventional teaching methods, IBL provides more meaningful learning experiences by promoting active participation and independent inquiry. However, several challenges remain, including the need for additional instructional time, teacher readiness, and the availability of adequate learning resources. Therefore, continuous professional development for teachers and sufficient institutional support are essential to maximize the effectiveness of Inquiry-Based Learning in elementary education settings. Keywords: Inquiry-Based Learning, Literacy, Numeracy, Critical Thinking, Elementary Education